Determinants, Impediments, and Opportunities for Organizational Sustainability in Kushtia’s Textile Industry - Rahman, Mostafizur; Hossain, Md Tuhin; Sima, Sunzida Akhter (European Journal of Applied Sciences, 2025)
The textile industry in Kushtia district serves as a significant source of revenue for this region of Bangladesh. It offers substantial employment opportunities and produces high-quality fabrics for both national and international markets. Nonetheless, this industry is currently facing multiple challenges and aims to achieve long-term sustainability. This study aimed to assess the problems, obstacles, and opportunities within a sustainable textile sector in the Kushtia region of Bangladesh. This research establishes a distinctive framework for the organizational sustainability of Kushtia’s textile industry. This research utilized a systematic literature review and adhered to the PRISMA framework, incorporating a comprehensive analysis to yield practical insights. The Scopus database was utilized to examine published research from 2020 to 2025, focusing on the keywords "organizational sustainability" and "textile industry." The research demonstrates the significance of sustainable leadership, green leadership, organizational learning, and organizational development for Kushita’s textile industry. The analysis indicates that Kushita’s textile sector in Bangladesh faces obstacles in management and leadership, challenges related to organizational learning and development, and deficiencies in personnel. The industry may leverage organizational learning and development to improve its sustainability. This study addresses the challenges and prospects of the sustainable textile sector in Kushtia, highlighting that environmental, social, economic, and political sustainability is achievable within the industry. This study introduces a novel framework that explores how sustainable leadership, green leadership, organizational learning, and organizational development interact to promote organizational sustainability in Kushtia’s textile industry. The research offers industry practitioners and government insights for improving sustainable leadership, green leadership, organizational learning, and organizational development to facilitate an effective transition to organizational sustainability in the textile industry. It can help governments and industry leaders create policies that balance environmental, economic, political, and social concerns. While confined to the Kushita region of Bangladesh, using secondary sources and excluding obscure materials, it sets a basis for studies in other growing economies.